Credit risk management practices at Citibank N. A : a case study from the perspective of credit policy guidelines of Bangladesh Bank - Shama, Lamia (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.